Thermal stability data of silver nanowire transparent conducting electrode - Chung, Choong-Heui (Data Brief, 2020)
The authors have recently reported the enhanced thermal stability of silver nanowire (AgNW) network transparent electrodes by electrodeposition method [1]. AgNW networks are known to break into droplets at elevated temperatures (spherodization temperature) that are still much lower than the bulk Ag melting temperature. This phenomenon is known as Rayleigh instability. As the diameter of individual AgNW in the network increases by electrodeposited Ag on the AgNW surface, the thermal stability of AgNW network can be enhanced. Here, we provide the data on the spherodization temperature depending on AgNW diameter. We also report the calculated activation energy required to induce the spherodization of AgNW network.